Jogo de identidades: a configuração publicitária de anunciantes e consumidores - Strassburger, Damaris (2012)
This research aims at examining in what ways brands configure their consuming public's identity via advertising in the contemporary context. For that, it departs from observing the adverts from both competitor brands over the same period of time: the ones from Coca-Cola and the ones from Pepsi. Considering that the main product offered by those brands - soda - is very similar, sold at identical prices and whose flavour is sometimes indistinguishable for the consumer, it seems pertinent to propose the hypothesis that what determines consumption of a certain brand as opposite to the other is related to the way of characterisation and interpolation of consumers, engraved in those brands's adverts, which, in a certain manner, interferes in the choices made by individuals. Such configuring elements of the consumers's image projected by the company would have the capacity to allow sudden identification of individuals aimed at by one of the brands - and not the other. Thus, this research's main objective is to comprehend the relations that are established by brands and their public as from the observation of televisual commercials vehicled by the before-mentioned companies. So that we can better visualise such a relation, we have defined the following specific objectives: (1) analyse discursive strategies employed in televisual adverts for brand and offered product characterisation; (2) identify values put on the agenda by those brands to interpolate the consumer; (3) look for configuring threads of the consuming public summoned by both brands in their interpolation process; (4) verify configuration of the consumption surroundings of those products proposed by commercials (elements and/or situations which involve type/habit of consumption), looking forward to better understanding the public in question. The analysis's steps include: (a) description of different Coca-Cola and Pepsi televisual adverts selected to compose our research corpus; (b) identification of themes and values involved in those texts; (c) examining of manipulating figures and discursive strategies employed in the narratives; (d) description of brand discursive configuration, of consuming public and of surroundings in which that consumption occurs (procedures of figurativisation, actoralisation, spacialisation, temporalisation and tonalisation). Employed methodology is inspired by discursive semiotics developed by the Greimasian group.